Epstein–Barr virus and thyroid cancer: The role of viral expressed proteins. Issue 4 (26th October 2018) - Moghoofei, Mohsen; Mostafaei, Shayan; Nesaei, Abolfazl; Etemadi, Ashkan; Sadri Nahand, Javid; Mirzaei, Hamed; Rashidi, Bahman; Babaei, Farhad; Khodabandehlou, Niloofar
Abstract : Background : Thyroid cancer is a common endocrine malignancy whose incidence has increased in recent years. Several internal and external risk factors are involved in the development of this cancer, such as infectious agents. Evidence supporting the role of viral infection as an etiology for the invasiveness of thyroid cancer is increasing. The aim of this study was to determine the presence of the Epstein–Barr virus (EBV) and the association between viral gene products and thyroid tumor development. Methods : Fifty‐seven thyroid cancer specimens were collected from the same number of patients as well as 18 samples from healthy controls. The presence of the EBV genome and the genotyping was examined by polymerase chain reaction (PCR). Also, an enzyme‐linked immunosorbent assay and real‐time PCR were used to measure the expression levels of viral and cellular genes. Results : The EBV DNA was detected in 71.9% of the samples, and it was also found that the presence of the EBV was associated with increasing development of thyroid tumor. Conclusion : Our results demonstrated that EBV infection may play a role in the development of thyroid tumor.